Agglomeration Economies and Firm Performance: The Case of Industry Clusters - Kukalis, Sal (Journal of Management, 2010)
Do firms located within an industry cluster outperform those that are not? Scholars of agglomeration economies have suggested that clustered firms stand to benefit from the positive externalities that stem from geographic proximity of industry. In this article, the relationship between agglomeration economies and financial performance is investigated. Thirty-one years of performance data for 194 firms from the semiconductor and pharmaceutical industries revealed no significant differences between clustered and nonclustered firms in the early stages of the industry life cycle. However, isolated (nonclustered) laggards outperformed clustered laggards in the late stages of the industry life cycle. Similarly, no significant differences in financial performance were found between the groups during periods of economic contraction at an early stage of the industry life cycle, but isolated firms outperformed clustered firms in the late stages of the industry life cycle. The reported results of this study, in combination with concerns raised by a few agglomeration scholars, suggest that the enthusiasm for cluster theory shown by scholars, practitioners, and policy makers may need to be tempered.